2021
DOI: 10.3390/su13084270
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Stance-Taking as a Sustainable Goal in Developing EFL Students’ Academic Writing Skills: Exploring the Effects of Explicit Instruction on Academic Writing Skills and Stance Deployment

Abstract: Effective stance-taking is considered as a crucial skill for successful academic writing and sustainable development of writing scholarship. However, student writers often encounter difficulties in this aspect. Scholars have thus called for explicit instruction to develop students’ academic writing ability as a sustainable goal. Learning stance-taking is a particularly relevant area of intensive interest among writing scholars. Yet, few empirical studies have been conducted to examine its effectiveness on stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Extensive reading and studying the linguistic choice of expert writers can offer student writers rich resources to construct theses writing. Empirical studies have shown that explicit instruction could sustainably benefit student writers' writing quality [42]. The expert bundles could be incorporated into writing lessons that might help students promote their expression in a more disciplinarily accepted way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive reading and studying the linguistic choice of expert writers can offer student writers rich resources to construct theses writing. Empirical studies have shown that explicit instruction could sustainably benefit student writers' writing quality [42]. The expert bundles could be incorporated into writing lessons that might help students promote their expression in a more disciplinarily accepted way.…”
Section: Discussionmentioning
confidence: 99%
“…Type Token SWC the ways in which *** − (12), the fact that the (11), the previous studies on (11), the relationship between the (11) 4 45 EWC the ways in which (42), the extent to which (23), the fact that the (21), the relationship between the (13) 4 99…”
Section: Np With Other Postmodifier Fragmentmentioning
confidence: 99%
“…Hyland found that EFL writers had problems with both the type and range of metadiscourse markers, affecting the persuasive effect of their argument [4]. Specifically, EFL student writers were less strategic in stance-taking for establishing persuasive argumentation [36]. Zhang and Zhan suggested that the EFL learners' voice development may be influenced by dynamic changes in culture, language, and education in a globalized society [37].…”
Section: Metadiscourse In Efl Academic Writingmentioning
confidence: 99%
“…Despite the existence of disciplinary conventions, it is provincial to regard writer identity as fixed. Instead, writer identity is constantly changing due to the reality of heteroglossia, reflected by the dynamic, dialogic interactions between writers, texts, and the prospective audience [36]. Writer identity is not mono-faceted either, for different aspects of identity are constructed simultaneously in a text through lexico-grammatical choice [31].…”
Section: Academic Writer Identitymentioning
confidence: 99%
See 1 more Smart Citation